Snakecharm / : 2 - Atwater-Rhodes, Amelia (Kiesha'ra Series, 2004)
The peace forged by the love between Zane and Danica, leaders of the avian and serpiente realms that had been at war for generations, is threatened by the arrival of Syfka, an ancient falcon who claims one of her people is hidden in their midst.